2015
DOI: 10.1039/c4ta06710j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one- and two-dimensional carbon hybridization of PEDOT:PSS on the power factor of polymer thermoelectric energy conversion devices

Abstract: Synergic effects of conducting polymers, carbon nanotubes, and graphene result in the enhanced thermoelectric properties of nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(74 citation statements)
references
References 34 publications
5
69
0
Order By: Relevance
“…The ZT value increased from 0.017 for pristine PEDOT: PSS to 0.031 for the PEDOT: PSS/graphene/MWNT composites. 104 The latest work on these ternary composites reports the effects of different weight ratio between PEDOT/graphene/carbon nanotube based ternary composite as well as the effects of acid treatment on the electrical conductivity and Seebeck coefficient. Electrical conductivities of 208.4 S.cm…”
Section: Graphene and Nanocomposite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ZT value increased from 0.017 for pristine PEDOT: PSS to 0.031 for the PEDOT: PSS/graphene/MWNT composites. 104 The latest work on these ternary composites reports the effects of different weight ratio between PEDOT/graphene/carbon nanotube based ternary composite as well as the effects of acid treatment on the electrical conductivity and Seebeck coefficient. Electrical conductivities of 208.4 S.cm…”
Section: Graphene and Nanocomposite Materialsmentioning
confidence: 99%
“…101 Graphene(rGO)/fullerene(C 60 ), 102 (rGO) 103 and, graphene/CNT/nano-composites 104,105 have been studied by several groups and prepared with PEDOT: PSS. The studies showed an increased power factor in all composites when compared with pure PEDOT: PSS due to an increased electrical conductivity/reduced thermal transport.…”
Section: Graphene and Nanocomposite Materialsmentioning
confidence: 99%
“…In a previous study, we demonstrated that the hybridization of one-dimensional CNTs and two-dimensional graphene platelets with PEDOT:PSS, using in situ polymerization, resulted in remarkably enhanced TE properties. 21 In this study, we investigated a exible and transparent lm using RTCVD graphene coated with a PEDOT:PSS conducting layer. The RTCVD graphene was transferred onto a PET substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Among the conducting polymers, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate), also known as PEDOT:PSS, is the most widely used material because of its high electrical conductivity, low band gap, and transparency in the visible region compared to those of others. [5][6][7] While most conducting polymers tend to be insoluble in any solvent, PEDOT:PSS can be dispersed in water and some polar organic solvents in the form of colloidal particles. This is because hydrophilic PSS acts as a charge-balancing counter-ion to stabilize hydrophobic PEDOT.…”
Section: Introductionmentioning
confidence: 99%